The impact of STEM experiences on student self-efficacy in computational thinking - Weese, Joshua L.; Feldhausen, Russell; Bean, Nathan H. (My University, 2016)
Since the introduction of new curriculum standards at K-12 schools, computational thinking has become a major research area. Creating and delivering content to enhance these skills, as well as evaluation, remain open problems. This paper describes two different interventions based on the Scratch programming language which aim to improve student self-efficacy in computer science and computational thinking. The two interventions were applied at a STEM outreach program for 5th-9th grade students. Previous experience in STEM related activities and subjects, as well as student self-efficacy, were collected using a developed pre- and post-survey. We discuss the impact of our intervention on student performance and confidence, and evaluate the validity of our instrument. © American Society for Engineering Education, 2016.
Citation: Weese, J. L., Feldhausen, R., & Bean, N. H. (2016). The impact of STEM experiences on student self-efficacy in computational thinking.
Keywords: Computational Thinking; Computer Science; Design; Self-Efficacy